Absenting - Kianna Marie McCoy; Susan Braude Stillman (Grounded Theory Review: An International Journal, 2021)
Absenting is defined as the father’s fear of what will happen to his child with autism when he is no longer living. The core variable, absenting, was discovered from data based on the main concern of fathers of children with autism. This is the first time in the literature that absenting has been used in association with fathers of children with autism. Fathers of children with autism face the future to resolve absenting in three ways: 1) preparing financially, 2) preparing for future living, and 3) preparing the child to live life to the fullest. Conditions affecting absenting are the severity of the disability and gender of the child. During the process of resolving their main concern, fathers experience self-transformation. This process includes three linear stages: 1) reaching out to the community, 2) balancing family relationships, and 3) helping others. Understanding the theory of absenting can help guide treatment and support for the child and family.